Evaluation of sterol transport from the endoplasmic reticulum to mitochondria using mitochondrially targeted bacterial sterol acyltransferase in Saccharomyces cerevisiae. Issue 10 (3rd October 2015) - Tian, Siqi; Ohta, Akinori; Horiuchi, Hiroyuki; Fukuda, Ryouichi
Abstract: To elucidate the mechanism of interorganelle sterol transport, a system to evaluate sterol transport from the endoplasmic reticulum (ER) to the mitochondria was constructed. A bacterial glycerophospholipid: cholesterol acyltransferase fused with a mitochondria-targeting sequence and a membrane-spanning domain of the mitochondrial inner membrane protein Pet100 and enhanced green fluorescent protein was expressed in a Saccharomyces cerevisiae mutant deleted for ARE1 and ARE2 encoding acyl-CoA:sterol acyltransferases. Microscopic observation and subcellular fractionation suggested that this fusion protein, which was named mito-SatA-EGFP, was localized in the mitochondria. Steryl esters were synthesized in the mutant expressing mito-SatA-EGFP. This system will be applicable for evaluations of sterol transport from the ER to the mitochondria in yeast by examining sterol esterification in the mitochondria. Graphical abstract: : A system to evaluate sterol transport from the ER to mitochondria by measuring sterol esterification catalyzed by a mitochondrially targeted acyltransferase was constructed.